PERENCANAAN PAJAK DAN IMPLIKASINYA TERHADAP USAHA MIKRO KECIL DAN MENENGAH (STUDI KASUS PADA UMKM MADU HUWAIDA) - Tiara Faradita; Nurul Aisyah Rachmawati (Pusat P2M Politeknik Negeri Batam, 2022)
This study plans and analyzes the implications of tax compliance for Micro, Small and Medium Enterprises with a case study on MSME Madu Huwaida. The purpose of this research is to help MSMEs to plan their obligations as taxpayers according to the provisions of the tax law. The type of qualitative research used is a case study. Data collection techniques used in the form of literature study, interviews, observation and documentation. The analysis technique used is in the form of data reduction analysis techniques, data presentation and verification. The results of the study show that based on the Law on the Harmonization of Tax Regulations, they are not required to pay taxes because their turnover has not yet reached the taxable turnover. Based on its tax obligations, namely the obligation to register, perform calculations, pay and report taxes owed, MSME Madu Huwaida has carried out its obligations as a taxpayer, which is marked by having a TIN as a taxpayer identification number. However, the tax obligations have not been fully carried out considering the limited resources and knowledge they have.